Therapeutic Effects of Aqueous Extracts of Cerasus Avium Stem on Ethylene Glycol- Induced Kidney Calculi in Rats - Azaryan, Ehsaneh; Malekaneh, Mohammad; Shemshadi Nejad, Maryam; Haghighi, Fatemeh (Urology Journal, 2017)
Purpose: To investigate the therapeutic effects of the aqueous extract of Cerasus Avium stem on kidney calculi. Materials and Methods: In this experimental study, forty-eight (48) male Wistar rats were randomly allocated into six (6) groups and were studied during a 30 day period. Group A served as normal control and Group B received 1% ethylene glycol in drinking water (EG group). C, D, E, and F Groups, received 1% ethylene glycol from day 1 and were used as prevention and treatment subjects. Rats in prevention groups of low dose (C) and high dose (D) extract, were gavaged with 200 and 400 mg/kg extract respectively from first day of the experiment and treatment groups of low dose (E) and high dose (F) extract, were gavaged with 200 and 400 mg/kg extract respectively from the 15th day of the experiment. Results: On the 30th days of the experiment, serum level of magnesium and potassium decreased significantly in EG group compared with A,C,D,E and F groups (P < .05), while serum level of calcium, creatinine, uric acid, sodium and urine level of calcium, creatinine, uric acid, increased significantly in EG group compared with A,C,D,E and F groups (P < .05). In the prevention and treatment groups, the number of deposits decreased significantly compared with EG group on the 30th day (P < .05). Conclusion: Cerasus Avium stem has a therapeutic effect on calcium oxalate stones in rats with nephrolithiasis and reduces the number of calcium oxalate deposits.